Skin impedance is not a factor in transcutaneous electrical nerve stimulation effectiveness - Vance, Carol GT (J Pain Res, 2015)
OBJECTIVE: Transcutaneous electrical nerve stimulation (TENS) is a nonpharmacological intervention used to manage pain using skin surface electrodes. Optimal electrode placement is unclear. We hypothesized that better analgesia would occur if electrodes were placed over sites with lower skin impedance. Optimal site selection (OSS) and sham site selection (SSS) electrode sites on the forearm were identified using a standard clinical technique. METHODS: Experiment 1 measured skin impedance in the forearm at OSS and SSS. Experiment 2 was a crossover design double-blind randomized controlled trial comparing OSS-TENS, SSS-TENS, and placebo TENS (P-TENS) to confirm differences in skin impedance between OSS and SSS, and measure change in pressure pain threshold (PPT) following a 30-minute TENS treatment. Healthy volunteers were recruited (ten for Experiment 1 [five male, five female] and 24 for Experiment 2 [12 male, 12 female]). TENS was applied for 30 minutes at 100 Hz frequency, 100 µs pulse duration, and “strong but nonpainful” amplitude. RESULTS: Experiment 1 results demonstrate significantly higher impedance at SSS (17.69±1.24 Ω) compared to OSS (13.53±0.57 Ω) (P=0.007). For Experiment 2, electrode site impedance was significantly higher over SSS, with both the impedance meter (P=0.001) and the TENS unit (P=0.012) compared to OSS. PPT change was significantly greater for both OSS-TENS (P=0.024) and SSS-TENS (P=0.025) when compared to P-TENS. PPT did not differ between the two active TENS treatments (P=0.81). CONCLUSION: Skin impedance is lower at sites characterized as optimal using the described technique of electrode site selection. When TENS is applied at adequate intensities, skin impedance is not a factor in attainment of hypoalgesia of the forearm in healthy subjects. Further investigation should include testing in patients presenting with painful conditions.